2004
DOI: 10.1016/s1573-5214(04)80022-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessing production constraints, management and use of sorghum diversity in north-east Ghana: a diagnostic study

Abstract: This paper reports on the results of a diagnostic study conducted to assess the problems and needs of sorghum farmers in north-east Ghana with the aim of determining the type of research that would be useful for them in their own context. The importance of the crop and its position within the cropping system are identified. Sorghum is still an integral part of the livelihoods of farmers. The crop is very versatile and not only contributes to food security but also plays a part in the socio-cultural, socioecono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 4 publications
2
23
0
Order By: Relevance
“…Several smaller studies highlighted the importance of Striga, poor soil fertility (including low nitrogen and phosphorus) and drought (especially water deficits during grain filling) among the most severe and widespread biophysical constraints to sorghum production in west, east and southern Africa (Chiduza et al 1995;Kudadjie et al 2004;Wubeneh and Sanders 2006). In South Asia the most severe constraints we identified agreed with those of Reddy et al (2007), who reported terminal drought, soil problems, and a range of insect pests and diseases to be important in India.…”
Section: Yields and Yield Gapsmentioning
confidence: 99%
“…Several smaller studies highlighted the importance of Striga, poor soil fertility (including low nitrogen and phosphorus) and drought (especially water deficits during grain filling) among the most severe and widespread biophysical constraints to sorghum production in west, east and southern Africa (Chiduza et al 1995;Kudadjie et al 2004;Wubeneh and Sanders 2006). In South Asia the most severe constraints we identified agreed with those of Reddy et al (2007), who reported terminal drought, soil problems, and a range of insect pests and diseases to be important in India.…”
Section: Yields and Yield Gapsmentioning
confidence: 99%
“…Despite the important role that the crop plays in the livelihood of populations in the country (Kudadjie et al, 2004), production is constrained by a myriad of biotic and abiotic factors, including insect pests, of which head bugs (Eurystylus oldi) constitute a major entity (Atokple, 1993;Gerda and Christopher, 2007;Ochieng et al, 2011).…”
Section: Sorghum (Sorghum Bicolor Moench) Ismentioning
confidence: 99%
“…Bandyopadhyay et al (2000) stated that while grain mould fungi may penetrate sorghum grain directly under high humidity conditions, infection by these fungi can be aided by biotic factors especially insects. Kudadjie et al (2004) noted that in the Upper East Region of Ghana, three sorghum varieties, namely Naga white, Framida and Kapaala, from the savannah Agricultural Research Institute (SARI) were introduced to farmers. A number of reasons, however, discouraged farmers from growing these improved varieties.…”
Section: Sorghum (Sorghum Bicolor Moench) Ismentioning
confidence: 99%
See 1 more Smart Citation
“…Since many rural livelihoods in sub-Saharan African countries depend, to a greater or lesser extent, on subsistence production of crops such as maize [14,15], it is important to understand the specific sources of aflatoxin exposure across diverse environments, in order to target adequately potential interventions. In Uganda, contamination by aflatoxin of many staple foods, including maize, cassava, groundnuts and locally manufactured baby foods (including baby soya and rice porridge) has been reported [8,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%